Support from friends moderates the relationship between repetitive negative thinking and postnatal wellbeing during COVID-19. (3rd September 2022) - Harrison, Virginia; Moulds, Michelle L.; Jones, Katie
ABSTRACT: Background: Increasing evidence has linked repetitive negative thinking (RNT) to postnatal depression and anxiety, yet the factors moderating this relationship have been minimally investigated. During the COVID-19 pandemic of 2020, social restrictions imposed to reduce viral transmission limited access to social support, which is critical to postnatal psychological wellbeing – potentially intensifying RNT. Objective: We examined whether perceived social support (from friends, family, and a significant other) played a moderating role in the relationship between RNT and maternal postnatal anxiety and depressive symptoms. Methods: A sample of women ( N = 251) who had given birth in the preceding 12 months completed an online battery of standardised measures during the COVID-19 'lockdown' of May 2020. Results: As predicted, social support moderated the relationship between RNT and depression such that the association between RNT and depression was stronger for women who reported lower levels of social support. Interestingly, this finding emerged for social support from friends only; for support from family and significant other, social support did not play a moderating role. Further, and unexpectedly, overall social support did not moderate the relationship between RNT and postnatal anxiety, however, social support from friends was a significant moderator. Conclusions: High levels of perceived social support from friends (but not family or significant others) buffered the effects of RNT on depression and anxiety during the postpartum period. Strategies to bolster peer social support may be a valuable inclusion in interventions to prevent and treat postnatal depression and anxiety.